New developments in cervical cancer screening and prevention (Blackwell Science, 1997)
The record of a joint EUROGIN and WHO experts meeting on cervical cancer, this book reviews the latest developments in the epidemiology, natural history and screening of cervical cancer. It also deals with mamanement of cervical cancer, the development of vaccines against human papilloma virus - its major causative agent - and new technologies such as automated screening, HIV testing ans adjustant tests to cytology. The final and most important part of the book reviews the consensus guidelines for cervical cancer developed by the experts as a result of meeting